The platform will undergo maintenance on Sep 14 at about 7:45 AM EST and will be unavailable for approximately 2 hours.
2022
DOI: 10.3389/fgene.2022.959291
|View full text |Cite
|
Sign up to set email alerts
|

Individual and combined effects of the GSTM1, GSTT1, and GSTP1 polymorphisms on type 2 diabetes mellitus risk: A systematic review and meta-analysis

Abstract: Backgrounds: Compared with previously published meta-analyses, this is the first study to investigate the combined effects of glutathione-S-transferase polymorphisms (GSTM1, GSTT1 and GSTP1 IIe105Val) and type 2 diabetes mellitus (T2DM) risk; moreover, the credibility of statistically significant associations was assessed; furthermore, many new original studies were published.Objectives: To determine the relationship between GSTM1, GSTT1, and GSTP1 polymorphisms with T2DM risk.Methods: PubMed, Embase, Wanfang,… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
1
1

Year Published

2023
2023
2025
2025

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(3 citation statements)
references
References 76 publications
0
1
1
Order By: Relevance
“…Although the genes found in the present study have been reported to be linked to T2DM risk in earlier studies [16,18], their genetic variants were not reported. Since many genetic variants are closely linked to each other, showing high LD (D' > 0.3), their genetic variants might be comparable to those reported in earlier studies [14,16].…”
Section: Discussioncontrasting
confidence: 64%
See 1 more Smart Citation
“…Although the genes found in the present study have been reported to be linked to T2DM risk in earlier studies [16,18], their genetic variants were not reported. Since many genetic variants are closely linked to each other, showing high LD (D' > 0.3), their genetic variants might be comparable to those reported in earlier studies [14,16].…”
Section: Discussioncontrasting
confidence: 64%
“…Earlier studies suggested that oxidative stress is linked to genetic and environmental factors, and their interaction results in the development of T2DM and its complications. The oxidative stress-related genetic variants of GPX1 , GPX3 , glutathione S-transferase ( GST )-theta-1 (GSTT1) , GST-mu1 (GSTM1) , arachidonate 5-lipoxygenase (ALOX5), and cytochrome β-245 alpha chain (CYBA) have been found to influence T2DM risk [ 6 , 17 , 18 ]. However, these studies were conducted in small groups of participants, and genetic variants related to oxidative stress and antioxidant systems have yet to be studied in larger populations.…”
Section: Introductionmentioning
confidence: 99%
“…This highlights that oxidative stress is a potential covariate in predicting patient response to antidiabetic treatment, and GSTP1 genotyping can be relevant for better identification of T2D patients who are likely to need specific pharmacological strategies focusing not only on lowering glucose [29], but also on oxidative stress. Many studies showed that Val allele of the GSTP1 Ile105Val polymorphism and the GSTP1 Val/Val genotype play an important role in individual susceptibility to T2D in different populations [4,[30][31][32][33][34][35], but only one study investigated the relationship between GSTP1 gene polymorphism and HbA1c level in T2D patients [31]. This study demonstrated no effect of polymorphism in the GSTP1 gene on glycemic control parameters, but in the population included in this study (n = 300) the GSTP1105Val/Val genotype, which significantly influenced the level of HbA1C in the Polish diabetic population, has not been detected.…”
Section: Discussionmentioning
confidence: 99%